Analysis of Students' Creative Thinking Skills in E-Portfolio-Based Economics Instruction - Mona Yelly Simamora; Sarwi; Arief Yulianto; Noening Andrijati; Indriana Eko Amaidi; Prima Lestari Situmorang (LPPM Universitas PGRI Semarang, 2026)
This study aims to analyze students' creative thinking skills in e-portfolio-based economics learning. Measurements were conducted using Torrance's creativity indicators, namely fluency, flexibility, originality, and elaboration. This quantitative descriptive study involved 30 grade X1 students at Jayapura State Senior High School who had studied material on banking and non-bank financial services institutions and the use of one class to maintain uniformity of learning treatment. Data collection techniques included observation and documentation. The instrument used in this study consisted of a creativity assessment rubric using a Likert scale of 1-4 with 16 creative thinking indicator items. The results of the study with the level of creative thinking ability in e-portfolio-based economics learning concluded that it had an average of 47.53 with a standard deviation of 2.83. The results of the project product assessment showed that the quality of the student group's product was in the good category with an average score of 81.25. Based on the results of the study, it was concluded that e-portfolio-based economics learning was able to encourage students to explore and develop creativity. This research is expected to provide an empirical basis for improving student creativity in accordance with the demands of the independent curriculum.